(untitled) (Journal of Technology and Operations Management, 2019)
Bakery industry has risen with the increasing demand of its products. This study aims to examine the students’ abilities in terms of cognitive, affective and psychomotor in supporting the competency needs in the bakery industry. This research tested the abilities required by the students during industrial training at the bakery stores. This research was conducted at four different bakeries in the area of Yogyakarta within May to July 2019. A total of 90 students participated in the survey. The findings show that a psychomotor ability is the highest skill needed in the bakery industry with 84%, followed by affective (81%) and cognitive (75.3%). This implies that psychomotor ability is the prominent domain in the bakery industry where it involves physical movement, coordination, and the use of motor-skills. This study helps the educational provider to give the correct knowledge to the students with the precise abilities for their future undertakings.